Reconstruction of the ZnAl Mixed Oxides Into the Layered Double Hydroxide Catalysts Active in the Aldol Condensation of Furfural: The Role of ZnO Particles - Dubnová, Lada; Daňhel, Rostislav; Meinhardová, Vendula; Korolova, Valeriia; Smoláková, Lucie; Kondratowicz, Tomasz; Kikhtyanin, Oleg; Čapek, Libor (Frontiers in Chemistry, 2022)
A memory effect is the ability to restore the original, lamellar layered double hydroxide (LDH) structure. Herein, we have described i) the changes in the structural and basic properties of ZnAl mixed oxides (MOs) during their transformation into ZnAl-reconstructed LDHs (RE-LDHs); ii) the extraordinary properties of ZnAl RE-LDHs compared to the original ZnAl LDHs; and iii) the changes of basic properties during the interaction of ZnAl RE-LDHs with atmospheric CO2. Aldol condensation was selected as probe reaction to prove the catalytic potential of ZnAl RE-LDHs. We have described a target method for preparing ZnAl RE-LDHs with a large number of basic sites. ZnAl RE-LDHs possess significantly higher furfural conversion in the aldol condensation of furfural than MOs. The structural, textural, and basic properties of the studied materials were described by temperature-programmed analysis, X-ray diffraction, N2 adsorption, temperature-programmed desorption of CO2, and in-situ diffuse reflectance spectroscopy.